Early diabetes screening via red blood cell mechanics using microfluidic chip integration - Yibo Feng; Bingchen Che; Yonggang Liu; Cangmin Zhang; Jiameng Niu; Jiangcun Yang; Guangyin Jing; Dan Sun; Xiaobo Gong; Ce Zhang (Mechanobiology in Medicine)
Early diagnosis of diabetes is crucial, as diabetes, particularly type 2, can eventually lead to irreversible changes and complications. Conventional techniques, such as the Fasting Plasma Glucose (FPG) Test and Hemoglobin A1c (HbA1c) Test, measure blood glucose levels, which fluctuate over time and are insensitive to early stages. In this study, we focus on measuring the mechanical properties of red blood cells, as their irreversible changes can indicate early pathological impacts of diabetes. We developed a microfluidic chip with a symmetrical hyperbolic structure. By periodically altering the state of the valve membrane, we generate a reciprocating shear flow field that repeatedly acts on groups of RBCs. We then quantify the morphological parameters of the RBCs, establishing a correlation between the reciprocating shear flow field and the morphological changes of the cells. Using the developed microfluidic chip, we investigated the resistance of blood cells from 20 healthy volunteers to mechanical stimuli. The results indicated a significant correlation between the deformability of red blood cells and age, while no such correlation was found among individuals of the same gender. This study highlights the potential of utilizing the mechanical properties of red blood cells as an early diagnostic tool for diabetes. Furthermore, given the ease of integration of microfluidic chips, they present a promising high-throughput diagnostic solution for large-scale clinical screening.